Reconciling the strategic goals of irrigated food production, energy production with environmental flows under water transfer project in the Yellow River Basin - Yichu Huang; Xiaoming Feng; Chaowei Zhou; Bojie Fu (Journal of Hydrology: Regional Studies)
Study region: The Yellow River Basin, China. Study focus: Reconciling the water, energy and land (WEL) nexus is critical for sustainable development. Pathways to reconcile the WEL nexus in river basins remain unclear due to limited comprehensive assessments. This study provides a quantitative investigation using an engineering-economic optimization method to explore how and to what extent the water transfer project reconciles irrigated food production, energy production with environmental flows in the Yellow River Basin. New hydrological insights: Maintaining environmental flows at 30 % of the river runoff will cause water for irrigation to be drained by energy production. Water transfer (∼2.8 km3/year) mitigates such trade-offs, decreasing water for the energy sector by 1.8 % (0.14 km3/year), replenishing water for agriculture by 0.5 % (0.09 km3/year), and decreasing groundwater use by 0.8 % (0.13 km3/year). (2) Water transfer also builds synergies between water consumption and the economic costs of energy production, with these co-benefits in the lower reaches spilling over to the upper and middle reaches. (3) Compared to irrigated food production, the operational costs of energy production are sensitive to water policies, implying that energy sector transformation is critical to sustainable pathways for reconciling the WEL nexus in the Yellow River Basin. Our study underscores the role of water transfer in alleviating water conflicts within the WEL nexus. Moreover, it provides valuable insights into transformative technological pathways toward a sustainable future in the Yellow River Basin and beyond.